Effects of Cooperative on The Performance of Small Scale Enterprises in Ikorodu Zone, Lagos State, Nigeria - Oluwakayode Peter Oluwasanya; OLUWAKAYODE PETER OLUWASANYA; Tawakalitu Abimbola Obasan; KAZEEM ADESINA SHITTU; ADEBISI FATIMOH AWOLUMATE (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2024)
Influence of cooperative on small scale enterprises performance is very crucial in facilitating credit access, promotion and development. It also aided small businesses in effectively utilizing the resources that were available. The study looked into small businesses' performance and cooperation in Lagos State, Nigeria's Ikorodu Zone. The design of the survey was descriptive. We gathered both primary and secondary data. A multi-stage sampling technique was used to schedule interviews and administer a well-structured questionnaire to 130 cooperative small-scale entrepreneurs. Descriptive and inferential statistical tools, including the mean, standard deviation, and Logit regression model, were used to analyze the collected data. The results demonstrated that operational difficulties can arise from noncompliance with legal and regulatory requirements supporting cooperative principles, and that poor management practices can impair the overall performance of cooperative entrepreneurs. Effective knowledge and skill transfer among small business owners is facilitated by cooperative engagement. For cooperative leaders, regular training as well as efficient governance and management techniques were advised. Keywords: Cooperative Societies, Performance, Small Scale Business, Credit Access, Ikorodu Zone